PERAN DAN KEWENANGAN PROFESI PENUNJANG PASAR MODAL (NOTARIS) DALAM MENGHADAPI ERA GLOBALISASI - Elvira Fitriyani Pakpahan; Vivi Prisilla; Dicky Dicky; Yuni Adriana Malau (STIH Putri Maharaja, 2020)
This study aims to examine the legal arrangements for the role and authority of the capital market supporting profession in the face of globalization, namely the notary public. Notary public is a public official who has the authority to make a contract deed or decision required by law to be made in confirmed documents. The position of a notary is regulated in Law No. 30 of 2004 which states that a notary public is the authorized official to make an authentic deed and other authorities. This study uses a normative juridical method that is analytical descriptive. The notary is authorized to make authentic deeds about all agreements, deeds, and stipulations that are required by legislation and / or that are desired by the parties concerned to be stated in the authentic deed. In addition, the notary must also ensure the certainty of the date of making the deed, keep the deed, give the grosse, copy and quote the deed, all of it as long as the making of the deeds are not also assigned or excluded to other officials.